Diffraction Efficiency Distribution of Output Grating in Holographic Waveguide Display System - Ao Liu; Yuning Zhang; Yishi Weng; Zhongwen Shen; Baoping Wang (IEEE Photonics Journal, 2018)
Planar waveguide structure has benefits to expand the exit pupil of the near-eye display. To achieve a uniform output luminance within the expanded exit pupil, a specific distribution of diffractive efficiency (DE) should be set for the out-coupling grating. In this paper, a physical model is built to study the DE distribution of out-coupling grating with consideration of the whole field of view. Compared to the previous works, which only considered the central view angle, this model is more consistent with the actual situations to realize a uniform imaging output for a waveguide-based near-eye display system. Also, a planar waveguide with two holographic volume gratings as the in- and out-coupling gratings is fabricated to verify the proposed DE distribution. In experiments, a spatial light modulator is applied as the spatial luminance modulator, and the coupling grating with the proposed DE distribution is fabricated by the holographic interference exposure setup. The results show a high consistency between the simulation and the experiment.